Pneumocystis jiroveci prophylaxis in patients undergoing Bendamustine treatment: the need for a standardized protocol. Issue 4 (9th February 2015) - Abkur, Tarig Mohammed; Saeed, Mamoun; Ahmed, Saad Zeinalabdin; McArthur, Ryan; Leahy, Maeve; O'Leary, Hilary; O'Keeffe, Denis
Key Clinical Message The decision for PJP prophylaxis depends on a physician's evaluation of multiple variables. The high rate of PJP infection described in this article combined with the known impaired T‐cell function post Bendamustine treatment justifies considering all patients for PJP prophylaxis when they receive Bendamustine treatment.